In vivo and in vitro effects of phaleria macrocarpa (scheff.) boerl on low density lipoprotein and pcsk9 expression - Chong, Soo Ching (2011)
Phaleria macrocarpa.iPm) fruit is traditionally used to treat high cholesterol level. .However itsanti-hypercholesterolemic property is still unknown. LDL receptor is a ligand that involves in the cholesterol metabolism by taking in LDL which has -high proportion of cholesterol whereas PCSK9 is a protein that mediates the degradation of LDL receptor. This study investigat-ed the effects of Pm fruit aqueous extract on weight control and mechanistic basis of its anti-hypercholesterolemic effect in both in vivo and in vitro conditions. In vivo study, 36 male Sprague dawley rats were randomized to 6 groups. 5 groups were given 3% (v/v) cholesterol enriched-diet for 52 days to induced to become hypercholesterolemia, followed by Pm fruit aqueous extract (0, 20, 30 and 40 mg -extract/kg bw) or .simvastatin (40 mg/kg) treatment for 84 days. The sixth group was used as a negative controL The effects of Pm fruit aqueous extr-acttreatment were determined on the following parameters: 1) body weight, 2) liver weight 3) liver weight-to-body weight ratio 4) blood lipid profiles (TC, TG: HDL and LDL) and 5) expression level of hepatic LDL receptor (160 kDa and 120 kDa) and PCSK9 proteins. Pm fruit aqueous extract significantly (p<0.05) reduced body weight gain but tends to reduce liver weight and liver weight-to-body weight ratio. As for the blood lipid profiles, 20 mgextract! kg bw of Pm significantly (P<0.05) reduced TC (1.54 mmol/L), TG (0.38 mmol/L), HDL (0.68 mmol/L) and LDL (0.94 mmollL) -whereas 30 mg extract! kg bw of Pm significantly (p<0.05) reduced TC (1-.55 mmol/L), TG (0.33 mmol/L) and LDL (0.93 mmol/L) as compared I to the untreated hypercholesterolemic group [TC (2.4 mmol/L), TG (1.13 mmol/L), HDL JO.94 mmollL) and LDL-(1.51 mmol/Lj], 40 mg. extract! kg bw of Pm signiIicantly-(p<0.05) reduced TC (1.85 mmol/L) and LDL (1.03 mmol/L). On the other hand, 20 mg extract! kg bw of Pm significantly (P<0.05Y increased LDL receptor and PCSK9 proteins by l-fold whereas 30 and 40 mg extract! kg bw of Pm had no effect on LDL receptor and PCSK9. Effect of Pm fruit aqueous extract in- in vivo model was then further analyzed in in vitro study. In vitro study, HepG2 cells were cultured in serum-free RPM! 1640, supplemented with 0.2% BSA with or without LDL (200 llM) and in the presence of Pm fruit aqueous extract (0, 0.1,2,40 and 1000 ug/ml) or simvastatin (10 llM) for 24 hours. The abundance of both LDL receptor (1-60 kDa) and -PCSK9 proteins and mRNA were then investigated. Similar to the in vivo study, Pm fruit aqueous extract was found to have increased -LDL receptor and PCSK9 proteins by l-fold in HepG2 cells with significant increment (P<0.05) at the concentration of 0.1 ug/ml. Besides that, Pm fruit aqueous extract at the concentration of 0.1 ug/ml also significantly (P<0.05) increased both LDL receptor and PCSK9 mRNA transcripts, comparable to simvastatin treated group. These study indicated that Pm fruit aqueous extract reduces body weight gain, liver weight, liver weight-to-body weight ratio and exhibited anti-hypercholesterolemic effect by reducing blood lipid profile of hypercholesterolemic rats and upregulating LDL receptor and PCSK9 at both protein and rnRNA level.